An investigation of squeeze film bearings - Staples, Bernard Christopher (2020)
This thesis describes both a theoretical and an experimental investigation of the behaviour of squeeze film bearings. Squeeze film bearings are commonly used to damp and isolate rotor vibration in gas turbine aero engines. The main objectives of the work are: a) to understand the behaviour of the squeeze film itself under representative conditions b) to verify the behaviour in a purpose built test rig c) to provide an analytical method for squeeze films, correlated by the rig tests, that when later integrated into whole engine rotordynamic models will give reliable predictions of engine response in a convenient and timely manner The analysis method developed in this thesis is based on a Finite Difference representation of the Reynolds lubrication equation, with adaptations to represent the boundary conditions realistically. To gain insight into the squeeze film behaviour and so guide the development of the Finite Difference analysis, Computational Fluid Dynamics (CFD) analysis was carried out for a two land squeeze film with central circumferential oil supply groove. The CFD analysis highlighted the role of inertia effects in the oil flow in the central groove, and how the groove oil flow greatly influences the boundary conditions and hence the pressures in the squeeze film lands.